ETIOLOGY, PATHOGENESIS AND CLINICAL DIAGNOSIS OF PEYRONIE’S DISEASE - Тарас Валерьевич Шатылко; Владимир Михайлович Попков; Александр Юрьевич Королев; Олеся Владимировна Крылова (Медицина в Кузбассе, 2017)
Peyronie’s disease remains an understudied progressing disease being  one of the relevant problems of modern urology and andrology. This condition may cause erectile dysfunction in men of fertile age and its negative impact on sexual function adversely affects patients’ quality of life. This article reviews epidemiology, pathophysiology and specifics of recording history and clinical diagnosis of Peyronie’s disease, that includes questionnaires, physical examination, evaluation of erectile function and penile deformity.